HUBUNGAN ANTARA PERUBAHAN VOLUME DARAH RELATIF DENGAN EPISODE HIPOTENSI INTRADIALITIK SELAMA HEMODIALISIS PADA GAGAL GINJAL KRONIK - Agustriadi, Ommy; Suwitra, Ketut; Raka Widiana, Gde; Sudhana, Wayan; Sidharta Loekman, Jodi; Kandarini, Yenny (journal of internal medicine, 2009)
Intradialytic hypotension (IDH) is a common complication in chronic hemodialysis (HD) patients, in turn would increase morbidity and mortality. Relative blood volume changes during HD play a role in IDH episode. Those changes can be assessed by total plasma protein measurement before and after HD. To determine relationship between relative blood volume changes (assessed by percentage of total plasma protein changes during HD) and IDH episode during HD in chronic renal failure, an analytical cross-sectional study was perferomed in 51 patients (28 males and 23 females, age 47.8 ±11.6 years) underwent chronic HD at Hemodialysis Unit of Sanglah Hospital Denpasar. Data were collected during single HD session. Blood pressure was measured every 30 minutes and relative blood volume changes assessed by measuring percentage of total plasma protein changes during HD. Among them, IDH episode experienced in 10 (19.6%) patients. Logistic regression analysis revealed a strong and significant relationship between relative blood volume changes and IDH episode during HD in chronic renal failure (Beta = 0.29; OR = 1.35; CI 95%: 1.1 - 1.6; p < 0.01) and it was found that every 1% changes in relative blood volume, would increase risk of hypotension episode by 35%. This relationship was still strong and significant (Beta = 0.46; OR = 1.58; CI 95%: 1.11 -2.25; p = 0.01) after adjusted by hemoglobin levels, intradialytic body weight changes, use of antihypertensive medi¬cations and diabetes melitus. Using ROC curve, found that optimal cut of point of intradialytic total plasma protein changes to predict an IDH episode during HD was 5.56% with 90.0% sensitivity and 80.5% specificity (95% CI: 0.83-0.99; p < 0.01). Our data revealed a strong and significant relationship between intradialytic relative blood volume changes assessed by intradialytic total plasma protein changes and IDH episode during HD in chronic renal failure.